Uniqueness theorems for algebraic functions that take the number of algebraic elements into account - Gol'dberg, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain uniqueness theorems for algebraic functions that take into account not only A-points but also the number of covering elements located above them.